2017
DOI: 10.2480/agrmet.d-14-00023
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of rice yield by SIMRIW-RS, a model that integrates remote sensing data into a crop growth model

Abstract: Food security has become a serious concern recently in Southeast Asia. The reduction of agricultural land because of economic development is decreasing the food supply. Simultaneously, due to rapid population growth, the food demand is increasing. Therefore, to ensure a stable food supply, it is important to estimate the supply capability of rice, which is the staple food in most Asian countries. In this study, a crop model (SIMRIW-RS) that can combine remote sensing data with a crop model (SIMRIW) was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…However, obtaining suitable optical satellite imagery is difficult because of the weather effects in cloudy areas [16]. To overcome the limitations of optical imagery, some studies used synthetic aperture radar (SAR) imagery to map the spatial distribution [17,18], crop height [19,20], and yield estimation of paddy rice [21][22][23]. Similar to the studies using optical imagery only, the integration of optical and SAR imagery for yield estimation also involved regression models [15,24] and artificial neural networks [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, obtaining suitable optical satellite imagery is difficult because of the weather effects in cloudy areas [16]. To overcome the limitations of optical imagery, some studies used synthetic aperture radar (SAR) imagery to map the spatial distribution [17,18], crop height [19,20], and yield estimation of paddy rice [21][22][23]. Similar to the studies using optical imagery only, the integration of optical and SAR imagery for yield estimation also involved regression models [15,24] and artificial neural networks [25].…”
Section: Introductionmentioning
confidence: 99%
“…RS data contain the growing condition of the crop at the observation time only, making it difficult to estimate crop yield directly [72]. In addition, although RS-based empirical forecasting models are relatively simple to build, these models cannot take into account temporal changes in crop yields without long-term field experiments [7].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have successfully demonstrated that SAR data can be used to monitor crop parameters. In a recent study conducted by Maki et al [99] they used LAI derived from SAR images of COSMO-Sky-Med satellite and integrate it in a crop model (SIMRIW) to successfully estimate rice yield at regional scale.…”
Section: Estimation Of Crop Parameters From Remote Sensingmentioning
confidence: 99%